(untitled) (Modern education and development, 2025)
Artificial Intelligence (AI) is one of the most transformative technologies of the 21st century. It refers to computer systems that simulate human intelligence to perform tasks such as learning, reasoning, problem-solving, and decision-making. This paper provides an overview of AI, discusses key applications in modern society, and examines ethical considerations involved in its development and use. The aim is to help students understand the foundations of AI and inspire critical thinking about its future